1980
DOI: 10.1029/jc085ic05p02861
|View full text |Cite
|
Sign up to set email alerts
|

Triggered lightning strokes originating in clear air

Abstract: During the 1978 campaign of the triggered lightning program at Saint‐Priyat d'Allier (France), simultaneous data from a movie camera, a coaxial shunt amperometer, a network of electric field mills, and a weather radar, were collected during the initial phase of a particular triggered event. These data are shown to exhibit a high degree of consistency, leading to the conclusion that charges totaling several coulombs were present in cloudfree air in the vicinity of a stormy area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 6 publications
3
15
0
Order By: Relevance
“…The actual position of the neutral point is unknown. Similar images were reported by Waldteufel et al (1980) and Saraiva et al (2014). In one case (Stroke 4; see Figure 4), the bidirectional leader and the RS were separated by a no-detectable-luminosity frame.…”
Section: Discussionsupporting
confidence: 79%
“…The actual position of the neutral point is unknown. Similar images were reported by Waldteufel et al (1980) and Saraiva et al (2014). In one case (Stroke 4; see Figure 4), the bidirectional leader and the RS were separated by a no-detectable-luminosity frame.…”
Section: Discussionsupporting
confidence: 79%
“…[42] The first four strokes of the Debby flash appear to have initiated between 2.8 km and 4.4 km in altitude. Waldteufel et al [1980] analyzed a triggered lightning flash in which 10 strokes were observed, using optical and electric field measurements, to originate in "clear air" at fairly low altitudes. The majority of the 10 strokes originated between 0.5 km and 2 km above ground level.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Of particular interest, a second return stroke followed the first after only 1.3 ms (bottom‐right panel of Figure ; see also, for reports on short interstroke intervals; Rakov & Uman, ; Saba et al, ; Uman & Voshall, ). LMA sources at the time of the second stroke and the ratio of the leader to return stroke field change indicate that the second stroke occurred in clear air below 1 km (see also, for reports of flashes in clear air; Krider, ; Waldteufel et al, ). Additionally, the final current pulse before the return stroke (bottom‐left panel of Figure ) does not have a coincident d E /d t pulse measured (typically due to stepping of the downward leader), suggesting that that current pulse is associated with stepping of the upward connecting leader (see also Biagi et al, , ; Guimaraes et al, ; Hill et al, ; Visacro et al, , ).…”
Section: Methodsmentioning
confidence: 98%